Indonesian students' participation in an interprofessional learning workshop - Ernawati, Desak Ketut; Lee, Ya Ping; Hughes, Jeff (2015)
Interprofessional learning activities, such as workshops allow students to learn from, with and about each other. This study assessed the impact on Indonesian health students' attitudes towards interprofessional education (IPE) from participating in a workshop on medication safety. The students attended a two-day IPE workshop on medication safety. Thirty-five (48.6%) students completed pre-/post-workshop surveys using a modified Readiness for Interprofessional Learning Scale (RIPLS) survey. The post-workshop survey also had a series of open-ended questions. Students' responses to each RIPLS statement pre-/post-workshop were compared, whilst their responses to open-ended questions in post-workshop survey were thematically analysed. Students reported positive attitudinal changes on statements of shared learning and teamwork sub-scale (Wilcoxon p value <0.05). Analysis of the open-ended questions indicated that students perceived the workshop as having improved their understanding on the importance of teamwork and communication skills. This study found that learning with other health students through an IPE workshop improved medical, nursing and pharmacy students' attitudes towards the importance of shared learning, teamwork and communication in healthcare service.